Finite mathematics : for management, life, and social sciences - Harshbarger, Ronald J.; Reynolds, James J. (Lexington, Massachusetts : D.C. Health and Company, 1989)
This desirable goal is not always an easy one to realize with students whose primary interest is in an area other than mathematics.
1. Sets, linear equations, and functions -- 2. Matrices -- 3. Inequalities and linear programming -- 4. Mathematics of finance -- 5. Introduction to probability -- 6. Introduction to statistic -- 7. Game theory.
Includes index.
Keywords: MATHEMATICS